Nuclear morphometric analysis in gastrointestinal stromal tumors: A preliminary study - Şükrü Oğuz ÖZDAMAR,; Sibel BEKTAŞ,; Sevim ERDEM ÖZDAMAR,; Gökhan GEDİKOĞLU,; Banu DOĞAN GÜN,; Burak BAHADIR, (Turkish Journal of Gastroenterology, 2019)
-